Pengaruh Daya Tarik Wisata, Fasilitas, dan Aksesibilitas terhadap Keputusan Berkunjung Wisatawan di Pantai Istana Amal Kabupaten Penajam Paser Utara - Rokhayah, Eka Gustiani; Ana Noor Andriana (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2021)
Tourist attraction, facilities, and accessibility are factors that determine success in the development of tourist destinations. Istana Amal Beach is a natural tourist destination located in Penajam Paser Utara Regency. Based on the data obtained by the researcher, it is known that there has been an increase and a decrease in tourist visits to the Istana Amal Beach due to the current COVID-19 pandemic. This study aims to determine the effect of Tourist Attractions, Facilities, and Accessibility on Tourist Visiting Decisions at Istana Amal Beach. The type of research used is associative with a quantitative approach. The data were analyzed using multiple linear regression analysis using SPSS version 22. The population in this study were visitors to Istana Amal Beach and followers of the Istana Amal Beach Instagram account whose exact number was unknown and the sample was taken using non-probability sampling with purposive sampling method, the number of samples was as much as 96 respondents. The results of the study obtained (1) Tourist attraction does not have a significant effect on Tourist Visiting Decisions at Istana Amal Beach; (2) Facilities have a significant effect on Tourist Visiting Decisions at Istana Amal Beach; (3) Accessibility has a significant effect on Tourist Visiting Decisions at Amal Palace Beach; and (4) Tourist Attraction, Facilities, and Accessibility together have a significant effect on Tourist Visiting Decisions at Istana Amal Beach.